Cytogenetic study of Meriz goat breeds in Iraqi Kurdistan region: Cytogenetic Meriz Goat Breeds in Iraqi region - Maghded Khdhr, Dilger; Jalal Karim, Karim (Cellular and Molecular Biology, 2024)
Goats are considered the leading farm animal that has a substantial role in the agricultural sector in the Kurdistan Region of Iraq. No cytological examination has been carried out on them. This experiment aims to identify the Karyotype of the local breeds of domestic goats. This experiment was conducted on the Karyotype and prepared the ideogram of Meriz goats. The determination of the relative length and centromeric index arm ratio of the chromosomes in the breed was achieved by the production of karyotypes. A total of (30)Meriz goats, consisting of (10) males and (20) females, were selected to collect blood samples for a short-term lymphocyte culture. The diploid chromosome count was observed to be (60), consisting of (29) pairs of acrocentric autosomes and one pair of allosomes, specifically the X and Y chromosomes. The acrocentric nature of the X-chromosome and the sub-metacentric nature of the Y-chromosome were identified through scientific investigation. The study observed a variation in the relative length of autosomal chromosomes in Meriz goats, with females ranging from 4.49% to 1.89% and males ranging from (4.53%) to (1.75%). The X-chromosome had a relative length of 3.96 in females, while the Y-chromosome displayed a relative length of (5.05). The findings of this karyological investigation suggest that the chromosomal composition seen in the Meriz goats under examination was within the expected range of normalcy. It is recommended that more cytogenetic analyses be conducted at the population level in order to identify individuals within the Meriz breed population who possesses numerical and/or structural chromosome abnormalities. This research is crucial for enhancing the efficiency of production and reproduction in this breed.